A comparative study to evaluate diagnostic accuracy and correlation between saline infusion sonography, hysterosalpingography and diagnostic hysterolaparoscopy in infertility - Tiwari, Arti; Singh, Beenu Kushwah; Mishra, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Till date hysterosalpingography (HSG) remains the first-line method to detect tubal patency and to find out any uterine abnormalities in infertile female while diagnostic hysterolaparoscopy (DHL) is considered to be the gold standard method, it is during last decades only that saline infusion sonography (SIS)/ sonohysterography (SHG) has emerged as an efficacious method of checking tubal patency and uterine anatomy as well. The present study aims to compare all three methods viz- SIS, HSG and DHL and to evaluate the correlation between these methods. Methods: 98 infertile females of age group 18-35 years with normal Hormonal profile without any male factor infertility, were prospectively selected from the outpatient department of obstetrics and gynecology, GMH Rewa, Madhya Pradesh over one year from 1st August 2016 to 31st July 2017. Results: Diagnostic accuracy (sensitivity and specificity) of SIS was found to be more than HSG for both tubal patency and uterine abnormalities detection. SIS has less numbers of false positive and false negative rates as compared to HSG. DHL was found to be much superior to both SIS and HSG, also detected additional findings in multiple sites like pelvis, tubes and the uterus on the same setting which were missed on SIS and HSG. Conclusions: SIS may replace HSG as a first step screening method for tubal patency detection, as it has more diagnostic accuracy than HSG and better correlation with DHL and has many advantages and minimal disadvantages as compared to HSG.